Oralidade e eventos de letramento relacionados à leitura: práticas sociais constitutivas da escrita - Maciel, Juliana Brosco de Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This research is the result of a senior research project and longed to verify if the ways of child‘s participation in orality in classroom and the literacy events related to reading would make possible to child construct a discursive relation with the writing. Besides it investigated the conception of 20 teachers from second year from primary school about orality and literacy and also identifies which theory purposes could be discerned in one of these teachers exercise. The methodology used was the qualitative approach, with exploratory- descriptive character, and based in system of references methodological of bibliographic research and collecting of facts research. The corpus of this research constituted in deflagrate element that stimulated the search for methodology answers which could clear the possible essence of set of problems evidenced. The results indicated that the ignorance of some basic conceptions that imbricate in teaching Portuguese language, principally in orality development, reading of writing by some individuals was alarming component parts, since many of them mediate the teachinglearning process of numberless individuals. Considering that orality and literacy play fundamental function in social interactions, this research has the intention to contribute for teacher‘s continuous formation, just as help them in development of students‘ linguistic competences, and elucidate them about the importance of literacy, besides to make public the more recently theoretical subsidies about this subject
Keywords: Linguagem; Oralidade; Letramento; Leitura; Escrita; Language; Orality; Literacy; Reading; Writing